Evidence of hormone resistance in a pseudo-pseudohypoparathyroidism patient with a novel paternal mutation in GNAS - BEREKET, ABDULLAH; HALİLOĞLU, BELMA; DEMİRCİOĞLU, SERAP (ELSEVIER SCIENCE INC, 2015)
Context: Loss-of-function GNAS mutations lead to hormone resistance and Albright's hereditary osteodystrophy (AHO) when maternally inherited, i.e. pseudohypoparathyroidism-Ia (PHPIa), but cause AHO alone when located on the paternal allele, i.e. pseudoPHP (PPHP). Objective: We aimed to establish the molecular diagnosis in a patient with AHO and evidence of hormone resistance. Case: The patient is a female who presented at the age of 13.5 years with short stature and multiple AHO features. No evidence for TSH or gonadotropin-resistance was present. Serum calcium and vitamin D levels were normal. However, serum PTH was elevated on multiple occasions (64-178 pg/mL, normal: 9-52) and growth hormone response to clonidine or L-DOPA was blunted, suggesting hormone resistance and PHP-Ia. The patient had diminished erythrocyte Gm activity and a novel heterozygous GNAS mutation (c.328 G>C; p.A109P). The mother lacked the mutation, and the father's DNA was not available. Hence, a diagnosis of PPHP also appeared possible, supported by low birth weight and a lack of AHO features associated predominantly with PHP-Ia, i.e. obesity and cognitive impairment. To determine the parental origin of the mutation, we amplified the paternally expressed A/B and biallelically expressed Gs alpha transcripts from the patient's peripheral blood RNA. While both wild-type and mutant nucleotides were detected in the Gs alpha amplicon, only the mutant nucleotide was present in the A/B amplicon, indicating that the mutation was paternal. Conclusion: These findings suggest that PTH and other hormone resistance may not be an exclusive feature of PHP-Ia and could also be observed in patients with PPHP. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Pseudohypoparathyroidism; Pseudopseudohypoparathyroidism; GNAS; Hormone resistance; XL-ALPHA-S; ALBRIGHT HEREDITARY OSTEODYSTROPHY; MATERNAL TRANSMISSION; GENE; PSEUDOPSEUDOHYPOPARATHYROIDISM; DEFICIENCY; G(S)ALPHA; IA; PATHOGENESIS; ASSOCIATION